PENINGKATAN NILAI TAMBAH DAN HARGA JUAL HIASAN DINDING BERBAHAN PERALATAN RUMAH TANGGA - Lidia Olga; Siti Kholifah; Taufik Rahman (SATKRIYA : Jurnal Pengabdian Kepada Masyarakat, 2024)
Home wall decorations come in a variety of shapes and the raw materials for making them. Some people like paintings to put on the living room walls, some frame photos of their extended family and even wall decorations made of wood. House wall decorations never seem to bore people to continue expressing themselves to create something new to put on the walls of the house. A variety of home wall decorations are offered by various manufacturers, ranging in price from tens of thousands to millions of rupiah. In this activity, what will be done is to increase the added value of wooden household equipment into wall decorations after undergoing a painting process and adding pictures so as to beautify the household equipment to be used as wall decoration at home. Many household appliances are sold in traditional markets at relatively affordable prices, ranging from IDR 10,000.00 to IDR 30,000.00. This household equipment will undergo a painting process and add other interesting images so that it looks beautiful and when installed on the wall of the house it will attract the attention of anyone who sees it. Household equipment that was previously only used as a cooking tool in the kitchen will move to the living room or family room.